Usefulness of laparoscopic right colectomy with intracorporeal anastomosis and preoperative weight reduction for ascending colon cancer in a severely obese patient. Issue 2 (21st December 2021) - Inaguma, Gaku; Tajima, Yosuke; Hiro, Junichiro; Hanai, Tsunekazu; Katsuno, Hidetoshi; Masumori, Koji; Koide, Yoshikazu; Matsuoka, Hiroshi; Endo, Tomoyoshi; Kamiya, Tadahiro; Chong, Yongchol; Sato, Harunobu; et al.
Abstract: Obesity has been considered a risk factor for postoperative complications following colorectal cancer surgery. However, the usefulness of a combination of intracorporeal anastomosis and preoperative weight reduction for severely obese patients with colon cancer remains unclear. A 66‐year‐old man with a body mass index (BMI) of 43 kg/m 2 presented with abdominal pain and iron deficiency anemia. Colonoscopy and computed tomography revealed advanced ascending colon cancer with regional lymph node metastasis and excessive abdominal fat. Preoperative diet‐induced weight reduction was performed for severe obesity, which decreased his BMI to 39.7 kg/m 2 after 1 month. Thereafter, curative resection was performed using intracorporeal anastomosis for reconstruction to achieve minimal colon and mesentery mobilization and a shorter incision. The patient was discharged from the hospital without complications. Laparoscopic right hemicolectomy combining intracorporeal anastomosis and preoperative weight reduction was extremely useful in the current patient with severe obesity and ascending colon cancer.